HUBUNGAN SIKAP PEGAWAI ATAS PELATIHAN DENGAN KINERJA PEGAWAI HOUSEKEEPING DI HOTEL GRAND ROYAL PANGHEGAR - Purba, Silvia Magdaleni (Jurnal Administrasi Bisnis, 2017)
ABSTRACTThe training will provide opportunities for employees to develop existing skills, learn new things so that to improve a good employee performance is certainly needed training. This study aims to investigate the relationship of employee attitude towards training and employee performance at Hotel Grand Royal Panghegar in Bandung. The type of the research used in this study is Rank Spearman correlational. Data were collected by conducting interviews to manager HRD and distributing questioners to 37 housekeeping employee at Hotel Grand Royal Panghegar. Analysis technique that used by writer in this study is descriptive analysis. The result of testing based on hypothesis the variable employee attitude towards training and performance employee Housekeeping Department have significant relationship as evidenced by the value significance t 4,050 > 2,028 (t table), and correlation coefficient > 0.5 – 0.75 which means the employee attitude on training and employee performance have a high relationship level.The conclusion of this study is that better the attitude of employees towards training then the better the performance produced. Within employee training system, the employee performance produced at Hotel Grand Royal Panghegar Bandung is good and in accordance with what is needed by the company.Keywords: training, employee performance